Modern Educational Technologies of Forming the Professional Competencies of Medical Students - Alisherovna, Azgarova Gulsum (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Today, the high demands placed on the level of training of specialists in the field of education emphasize the formation of professional competencies in students. In order to check the level of development of practical skills, it is suggested to use new educational technologies in the educational process. This article presents materials on the use of innovative teaching methods such as case-study method, role-playing and Web-quest for students of medical universities, and several stages of implementing the case method are highlighted.